Foreign agents? Natural resources & the political economy of civil society - Corinna Breyel; Theocharis Grigoriadis (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2016)
Resource-rich dictatorships are more inclined to repress civil society than others. In this paper, we identify a tradeoff between political rents from natural resources and the organizational density of civil society. This organizational density determines the extent to which citizens can threaten the dictator with a revolution. We find that, in the occurrence of a negative oil price shock, regime change becomes likely, whereas a positive oil shock increases the extractive capacity of the dictator. When a negative oil price shock occurs, the persecution of failed revolutionaries can prevent revolution if the probability of revolutionary success is already low ex-ante. Historical and contemporary illustrations are drawn from Iran, the Soviet Union/Russia and Egypt.
Keywords: C73; P36; P48; P51; Q34; 330; natural resources; dictatorship; civil society; organizational density; persecution